THYRSOIDEA MACRURA (BLEEKER), THE LONGEST GIANT MORAY EEL FROM THE INDIAN WATERS - Bande, V N; Kartha, K N Rasachandra (Indian Journal of Fisheries, 2011)
A specimen of the giant moray eel, Thyrsoidea macrura, measuring 3080mm in length (after preservation), obtained from Karwar is described. Thisappears to be the longest specimen of the species on record.